Editorial - Mattos, Amana; Souza, Alice De Marchi Pereira de; Ponciano, Edna Lúcia Tinoco; Bispo, Fábio Santos; Degani-Carneiro, Filipe; Hernández, Jimena de Garay; Quadros, Laura Cristina de Toledo; Brunhari, Marcos Vinicius; Wendling, Michelle Menezes; Hayasida, Nazaré Albuquerque; et al. (Estudos e Pesquisas em Psicologia, 2023)
Alice De Marchi Pereira de Souza, Amana Mattos, Edna Lúcia Tinoco Ponciano, Fábio Santos Bispo, Filipe Degani-Carneiro, Jimena de Garay Hernández, Laura Cristina de Toledo Quadros, Marcos Vinicius Brunhari, Michelle Menezes Wendling, Nazaré Albuquerque Hayasida, Patrícia Lorena Quitério, Rebeca Valadão Bussinger, Rodolfo Rodrigues de Souza, Rosana Lazaro Rapizo, Sabrina Dal Ongaro Savegnago, Vitor Castro Gomes